2020
DOI: 10.1007/s13524-019-00841-y
|View full text |Cite
|
Sign up to set email alerts
|

Family, Firms, and Fertility: A Study of Social Interaction Effects

Abstract: Research has indicated that fertility spreads through social networks and attributed this phenomenon to social interaction effects. It remains unclear, however, whether the findings of previous studies reflect the direct influence of network partners or contextual and selection factors, such as shared environment and common background characteristics. The present study uses instrumental variables to improve the identification of social interaction effects on fertility. Using data from the System of social stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Madhavan and Adams (2003), for instance, show that in Mali, not only are network effects on fertility much more pronounced for women aged 30 or older than for younger women, but the effects of social networks on contraceptive use are markedly different for these two groups. Such an association with fertility changes is also documented for Western nations, including Germany (Bernardi, Keim, & Klärner, 2014;, the Netherlands (Buyukkececi, Leopold, van Gaalen, & Engelhardt, 2020), Norway (Lyngstad & Prskawetz, 2010) and the US (Balboa & Barban, 2014;Fletcher & Yakusheva, 2016;Yakusheva & Fletcher, 2015). In the US, for instance, a 10 percentage point increase in peer pregnancies is linked to a 2-5 percentage point greater likelihood of an individual becoming pregnant (Fletcher & Yakusheva, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…Madhavan and Adams (2003), for instance, show that in Mali, not only are network effects on fertility much more pronounced for women aged 30 or older than for younger women, but the effects of social networks on contraceptive use are markedly different for these two groups. Such an association with fertility changes is also documented for Western nations, including Germany (Bernardi, Keim, & Klärner, 2014;, the Netherlands (Buyukkececi, Leopold, van Gaalen, & Engelhardt, 2020), Norway (Lyngstad & Prskawetz, 2010) and the US (Balboa & Barban, 2014;Fletcher & Yakusheva, 2016;Yakusheva & Fletcher, 2015). In the US, for instance, a 10 percentage point increase in peer pregnancies is linked to a 2-5 percentage point greater likelihood of an individual becoming pregnant (Fletcher & Yakusheva, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…It is therefore not self-evident why we should interpret the estimated effect as any more causal than that from a standard OLS. (This critique also goes for, for example, Buyukkececi et al 2020. )…”
Section: Examples Of Other Ivs Proposed In the Literaturementioning
confidence: 95%
“…Studies focusing on other family formation patterns include de Vuijst et al (2017) and McDermott et al (2013) where the influence of siblings and peers on divorce behavior are examined, respectively. In another study, Buyukkececi and Leopold (2020) investigated how siblings' fertility, marital, and divorce behavior are related to each other by not limiting social interactions to the same behavioral domain (e.g., fertility-fertility or divorce-divorce associations). Most of these studies found significant associations between network partners' family formation behavior.…”
Section: Former Spouse Influences On Re-partneringmentioning
confidence: 99%
“…To elicit these effects at the microlevel, studies have focused on networks such as siblings, friends, and colleagues and examined whether the transition to parenthood (Balbo & Barban, 2014 ; Buyukkececi et al, 2020 ; Lyngstad & Prskawetz, 2010 ), marriage (Buyukkececi & Leopold, 2020 ), and divorce (de Vuijst et al, 2017 ) spread among these network partners. Social interaction effects might similarly be relevant in explaining the emergence of new living arrangements such as re-partnering following a divorce or breakup.…”
Section: Introductionmentioning
confidence: 99%